Sikap Guru Dalam Mendukung Keberhasilan Pendidikan Inklusi - Ilena Dwika Musyafira; Wiwin Hendriani (Universitas Pendidikan Mandalika (UNDIKMA), 2021)
The aim of this study was to analyze teachers' attitudes towards inclusive education and how they impacted on the successful practice of inclusive education. This research was a literature review study with analysis descriptive techniques. Electronic data sources in the form of ScienceDirect, SAGE and Google Scholar were used to collect data. There were 12 journals in the last 10 years that met the criteria. The results showed that most journals suggest that teachers have a positive attitude towards inclusive education. The positive attitude of teachers towards inclusive education can be assessed from the readiness of the teacher to accept children with special needs into the classroom. Communities with a culture of individualism tend to have positive attitudes towards inclusive education and can accept special needs children into the classroom. Experience, length of teaching and training affect differences in teacher attitudes towards inclusive education. Self-efficacy is found to be closely related to teachers' attitudes towards inclusive education.